THE EFFECT OF TEACHER'S EXAMPLE ON THE MORALS OF MADRASAH STUDENTS ALIYAH NURUL AS'ADIYAH CALLACCU SENGKANG, WAJO REGENCY - Andi Baso Muammar Assaad; Syarifuddin Ondeng; A. Marjuni (Universitas Islam Negeri Alauddin Makassar, 2022)
This study discusses the effect of the teacher's example on the morals of the students of Madrasah Aliyah Nurul As'adiyah Callaccu Sengkang, Wajo Regency. The type of research used in this research is ex-post facto quantitative. Ex-post facto research is research in which the independent variables have been treated, or treatment was not carried out at the time of the research, so this research is usually separated from experimental research. This quantitative research aims to find out how much influence between variables. In this study, the research will examine the effect of teacher's example on the morals of the students of Madrasah Aliyah Nurul As'adiyah Callaccu Sengkang, Wajo Regency. The example of the teacher is very influential on the morals of students, therefore a teacher is required to continue to show good examples, the example of the teacher is needed with the aim that students have good morals.